A feasible unemployment-based shock absorber for the Euro area - Andrea Brandolini; Francesca Carta; Francesco D'Amuri (Institute for the Study of Labor (IZA), 2015)
This paper contributes to the debate on the design of a centralised fiscal tool absorbing country-specific negative shocks in the euro area. Based on theoretical insights, it identifies the broad characteristics that a shock absorber based on unemployment should have in order to be incentive-compatible and politically feasible. It then derives empirically the combination of activation thresholds, experience rating, eligibility criteria, and benefit generosity which define the systems offering the highest stabilisation for given levels of redistribution, accounting for the large variation in benefit take-up rates across European countries. The analysis suggests that the shock absorber should: i) give rise to macro cross-national transfers, mimicking those that would be generated by a notional euro-wide unemployment benefit scheme of minimal coverage and generosity; ii) be activated by a trigger; and iii) feature partial experience rating. The simulation results, confirmed by robustness checks, show that even systems that do not redistribute resources between countries can have a non-negligible stabilisation impact in the medium run. Low benefit take-up rates in Southern Europe substantially reduce the stabilisation properties and the size of the scheme.
Keywords: E6; J65; H53; 330; unemployment benefits; absorption of macroeconomic shocks; fiscal union